2021
DOI: 10.20517/2574-1209.2020.48
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of oxidative stress and ARMS2-HTRA1 genetic risk in neovascular AMD

Abstract: Age-related macular degeneration (AMD) is the leading cause of vision loss in adults over 60 years old globally. There are two forms of advanced AMD: “dry” and “wet”. Dry AMD is characterized by geographic atrophy of the retinal pigment epithelium and overlying photoreceptors in the macular region; whereas wet AMD is characterized by vascular penetrance from the choroid into the retina, known as choroidal neovascularization (CNV). Both phenotypes eventually lead to loss of central vision. The pathogenesis of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 153 publications
(169 reference statements)
0
17
0
Order By: Relevance
“…These variants are in high linkage disequilibrium (LD), and most studies to date have been unable to statistically distinguish between them. It is therefore unclear to date which of ARMS2 or HTRA1 is responsible for increased AMD risk [ 306 ]. Moreover, the exact structure and function of ARMS2 and HTRA1 remain unclear.…”
Section: Genes Implicated In Multiple Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…These variants are in high linkage disequilibrium (LD), and most studies to date have been unable to statistically distinguish between them. It is therefore unclear to date which of ARMS2 or HTRA1 is responsible for increased AMD risk [ 306 ]. Moreover, the exact structure and function of ARMS2 and HTRA1 remain unclear.…”
Section: Genes Implicated In Multiple Pathwaysmentioning
confidence: 99%
“…Local ARMS2 dysfunction may play a role in oxidative stress and damage to the retina [ 306 , 307 ]. Early studies suggested that ARMS2 localizes to the outer mitochondrial membrane in photoreceptors and RPE cells [ 302 , 307 , 308 ], although this finding has been disputed [ 309 , 310 ].…”
Section: Genes Implicated In Multiple Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Endogenous local oxidative stress factors on the RPE and retina include the daily renewal and digestion of (oxidized) photoreceptor outer segments, their intrinsically high metabolic rate, high dissolved oxygen concentration, and dependency on mitochondrial oxidative phosphorylation for proper function [ 35 , 36 ]. As a result, with aging, the RPE contains relatively high concentrations of oxidation-modified lipids and proteins, which probably contribute to the development of AMD over time [ 35 , 37 , 38 ]. Moreover, as people age, BrM’s permeability also decreases and a lipid wall builds up, hindering the reciprocal transport of nutrients and (oxidized) waste products between the RPE to the choroid [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%